MESIN TETAS TENAGA SURYA PADA PETERNAKAN ITIK ALABIO DI KECAMATAN GAMBUT KABUPATEN BANJAR - Achmad Jaelani; Neni Widaningsih; Muhammad Firman (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
Breeding ducks Alabio not be separated from the activities of the hatch, but theproductivity in generating Day Old Duck (day old ducklings) on hatching activity remainslow. This is due to some problems in the hatchery that often the death of the electricity sothat the temperature and humidity of the incubator is not constant during hatching. This willaffect the duck embryonic development. Besides, reversal and provision of high humidity isstill done manually so that the eggs are often removed from the incubator. Reversal of eggsis essential to prevent embio attached to the shell. South Kalimantan is a tropical regionwith year-roundsunshine. It can be stored to be utilized as a source of energy through theconversion of solar energy into heating the incubator. Aside from the use of solar energybecomes a substitute for the electricity and can last up to 15 years without having to paysubscription fees and usage of electricity. Solar power conversion technology can overcomethe limitations of the heater in the incubator in the District Peat Banjar district, in additionto the modifications to the reversal of eggs and automatic sprayer. With this expectedproductivity hatchery to produce DOD will be higher. Yet another obstacle arises whenDOD high productivity being offset by marketing efforts. For that partners business groupsales of poultry Setia Budi prepared to be a partner in marketing the Day Old Duck (DOD),which previously only market the consumption of duck eggs. Measuring the success of thisactivity is to look at the operation of the incubator solar power during the 28 days prior tohatching without any outages, as well as the percentage of eggs that hatch, number of DODthat hatch in a healthy condition, business analysis more efficient hatching and the numberof DOD that could be marketed.